1997
DOI: 10.1083/jcb.139.2.541
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a Truncated, Kinase-Defective TGF-β Type II Receptor in Mouse Skeletal Tissue Promotes Terminal Chondrocyte Differentiation and Osteoarthritis

Abstract: Members of the TGF-β superfamily are important regulators of skeletal development. TGF-βs signal through heteromeric type I and type II receptor serine/threonine kinases. When over-expressed, a cytoplasmically truncated type II receptor can compete with the endogenous receptors for complex formation, thereby acting as a dominant-negative mutant (DNIIR). To determine the role of TGF-βs in the development and maintenance of the skeleton, we have generated transgenic mice (MT-DNIIR-4 and -27) that express the DNI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
362
0
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 450 publications
(379 citation statements)
references
References 69 publications
14
362
0
3
Order By: Relevance
“…Many growth factors and cytokines have been shown to influence the pathogenesis of osteoarthritis (14), such as transforming growth factor ␤ (TGF-␤) (16)(17)(18)(19)(20)(21)(22) and bone morphogenetic proteins (BMPs) (23). In addition, genetic predisposition to osteoarthritis has been linked to mutations in genes like COL2A1 (24).…”
Section: Resultsmentioning
confidence: 99%
“…Many growth factors and cytokines have been shown to influence the pathogenesis of osteoarthritis (14), such as transforming growth factor ␤ (TGF-␤) (16)(17)(18)(19)(20)(21)(22) and bone morphogenetic proteins (BMPs) (23). In addition, genetic predisposition to osteoarthritis has been linked to mutations in genes like COL2A1 (24).…”
Section: Resultsmentioning
confidence: 99%
“…MMP13 is the main collagenase that cleaves type II collagen in articular cartilage leading to OA (Reboul et al 1996;Billinghurst et al 1997). Expression of a truncated form of TbRII (Serra et al 1997) or silencing Smad3 expression (Yang et al 1999) also results in an OA phenotype in mice, further showing the importance of TGF-b signaling in the maintenance of joint homeostasis. OA is observed in all characterized etiologies of LDS (mutations in TGFBR1, TGFBR2, SMAD3, and TGFB2), but appears to be particularly frequent in pa-…”
Section: Dysregulation Of Tgf-b or Bmp Signaling In Catabolic Bone DImentioning
confidence: 99%
“…TGFb signaling controls longitudinal bone growth through inhibition of chondrocyte terminal differentiation and maintenance of the proliferating chondrocyte pool (Serra et al 1997;Alvarez et al 2001;Yang et al 2001;Alvarez and Serra 2004). Consequently, conditional inactivation of Tgfbr2 or Tgfbr1, which leads to ablation of TGF-b signaling, results in severe shortening of the limbs among other skeletal manifestations (Baffi et al 2004;Seo and Serra 2007;Matsunobu et al 2009;Hiramatsu et al 2011).…”
Section: Regulation Of Chondrogenesis and Longitudinal Bone Growth Bymentioning
confidence: 99%
“…In an animal model of OA, TGF␤RII expression was shown to be dramatically decreased during advanced phases of the disease (17). In other studies, transgenic mice expressing a truncated TGF␤RII in skeletal tissue were shown to develop cartilage degenerative symptoms similar to that of OA in humans (18).…”
mentioning
confidence: 93%